Uma outra leitura da Arquitectura através do olhar fotográfico: A narrativa visual nas estações de Metro da Cidade do Porto - Ana Paula Duarte Camilo (2019)
The present dissertation concerns a discourse's production through a set of Visual Narratives that intend to represent Architecture through Photography, resulting in two sets of documents: the first with the dissertation that's here presented, and the second with a group of three visual narratives that corresponds to the photographic project developed. The photographic image, besides being a communication support between people, goes also for intercession between men and what surrounds him. In other words, beyond its power of communication has also the capacity to establish a connection between Men and the World, between Men and Space, between Men and Architecture. We assume here the importance that the photographic image has revealed throughout its History as a tool of architectonic comprehension, seeking to achieve that importance through the construction of a critical and artistic visual discourse about the Architecture in issue, the Porto's Metro stations.